Analisis Sikap Mandiri, Motivasi, Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Studi Kasus Pada Mahasiswa Prodi Manajemen Universitas Proklamasi 45 - Niken Widyastuti (CV. Aksara Global Akademia, 2023)
This research aims to analyze student entrepreneurial activities. Specifically, the target of this research is to determine the independent attitude, motivation and knowledge of entrepreneurship towards the entrepreneurial interest of students at the Faculty of Economics, University of Proclamation 45 (UP45). The type of research used in this research is qualitative research with a phenomological approach. The information obtained was in the form of written and verbal data from informants. Meanwhile, the data collection techniques used in this research are observation and interviews. The number of respondents was 7 Management students class of 2021 who took entrepreneurship classes. The results of this research show that increasing interest in entrepreneurship for students at the UP45 Faculty of Economics can be done by conducting structured entrepreneurship lectures, guest lectures, entrepreneurship internships, and student creative programs, while students' efforts to start a business begin with finding product ideas first, discovering partners and links to work together, then the process of creating products.